Phobias : the psychology of irrational fear - Milosevic, Irena (Clinical psychologist); McCabe, Randi E. (Santa Barbara, California : Greenwood, an imprint of ABC-CLIO, LLC, 2015)
"Combining popular appeal with accessibly written entries suitable for research projects, this fascinating encyclopedia provides a thorough introduction to the psychological and scientific aspects of phobias"--
Includes bibliographical references and index.
Keywords: Phobias -- Encyclopedias; Anxiety disorders -- Encyclopedias